Utilization of preventative health checkup services in China among middle-aged and older adult population: evidence from China’s 28 provinces - Jingyu Shen; Jingyu Shen; Weiji Fang; Weiji Fang; Yating Zhu; Yating Zhu; Chunli Ye; Chunli Ye; Yanhua Zhu; Yanhua Zhu; Yanling Tao; Yanling Tao (Frontiers in Public Health)
IntroductionResearch on the utilization of outpatient and inpatient medical and health services for residents and the factors influencing them is well established, however, there are fewer relevant studies analyzing the utilization of preventive health check-up services for middle-aged and older adult people in China. In this study, we hope to understand the utilization of preventive health care services and identify the factors that influence such utilization, thereby providing insights for health policy and resource allocation.MethodsThe study uses data from the 2020 CHARLS survey, including 17,200 participants aged 45 and older.ResultsApproximately 47.3% of middle-aged and older adult individuals had at least one health checkup. Utilization was significantly influenced by age, area of residence, education level, social insurance, health insurance, personal income, presence of chronic diseases, and life satisfaction. Older adults, urban residents, and individuals with higher income or chronic conditions were more likely to utilize health checkup services.ConclusionThere are significant urban–rural disparities in the utilization of health checkup services among middle-aged and older adult people in China. Future health policies should prioritize rural areas and disadvantaged groups to improve equity and accessibility of health services.